FLEXIBILITY AND ROLE OF TASK-BASED LANGUAGE TEACHING IN EDUCATION - Tog’ayev Bobur Erkin o’g’li; Muxammadiyeva Madina Jamoliddin qizi (The Conference Hub, 2025)
Task-Based Language Teaching (TBLT) is all about putting learners at the center of the learning experience, emphasizing real communication through engaging in practical tasks. This article delves into how the concept of a "task" within TBLT has evolved over the years, highlighting the distinction between standard language exercises and authentic pedagogical tasks. Drawing from both theoretical insights and classroom experiences, it examines the spectrum of tasks, ranging from drills focused on form to activities centered on communication. Additionally, it touches on the cognitive and sociocultural theories that underpin TBLT, how educators implement it in various classroom settings, and the hurdles they encounter when trying to adapt TBLT to their unique educational and cultural contexts. By broadening the definition of what constitutes a task, this paper aims to empower teachers to apply TBLT in a more adaptable and effective manner.
Keywords: Task-Based Language Teaching (TBLT), Communicative Language Teaching, Language Tasks, Form-focused vs Meaning-focused Activities, Language Learning Continuum, Sociocultural Theory, Cognitive Perspectives in SLA, Classroom Challenges, Language Output, Task Adaptation in Education.